Straight to Jesus Sexual and Christian Conversions in the Ex-Gay Movement. - Erzen, Tanya (Berkeley : University of California Press, 2006)
Focuses on the everyday lives of men and women at New Hope Ministry, a residential ex-gay program. This study traces the stories of people who have renounced long-term relationships and moved from other countries out of a conviction that the conservative Christian beliefs of their upbringing and their own same-sex desires are irreconcilable.
Contents; List of Abbreviations; Introduction; 1. Steps Out of Homosexuality; 2. New Creations; 3. A Refuge from the World; 4. Arrested Development; 5. Testifying to Sexual Healing; 6. Love Won Out?; Conclusion: Walking in a Dark Room; Acknowledgments; Notes; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W.
Print version record.
Includes bibliographical references and index.
Keywords: New Hope Ministries -- Case studies; New Hope Ministries -- Case studies; New Hope Ministries; Church work with gays -- California -- San Rafael -- Case studies; Ex-gay movement -- California -- San Rafael -- Case studies; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Church work with gays; Ex-gay movement; California -- San Rafael; Electronic books; Case studies